Assessment and comparison of CHADS2, CHA2DS2-VASc, and HAS-BLED scores in patients with atrial fibrillation in Saudi Arabia - Al-Turaiki, Abdulrahman M. (Ann Thorac Med, 2016)
AIMS: No previous reports on the utilization of CHADS2, CHA2DS2-VASc, and HAS-BLED scores in atrial fibrillation (AF) patients in Saudi Arabia have been identified in the literature. The main objectives of this study were to assess and compare the distribution of CHADS2, CHA2DS2-VASc, and HAS-BLED scores and to identify the most common risk factors for stroke and bleeding among AF patients attending clinical pharmacists managed anticoagulation clinic. SETTINGS AND DESIGN: This cross-sectional study was conducted over 2 months period at clinical pharmacists managed anticoagulation clinic. METHODS: CHADS2, CHA2DS2-VASc, and HAS-BLED scores were calculated and compared for all eligible patients. RESULTS: Two hundred and sixty-four patients with AF were included in the analysis. The number of patients at low risk for stroke was found to be 14 (5.3%) using CHADS2 and only 4 (1.5%) using CHA2DS2-VASc. On the other hand, 64 patients (24.2%) were found at moderate risk for stroke using CHADS2 compared with 17 patients (6.4%) using CHA2DS2-VASc. Most of the patients were found to be at high risk for stroke using either the CHADS2 (70.5%) and CHA2DS2-VASc (92%). The study also revealed that most of the patients were at moderate (63.3%) to high (27.7%) risk of bleeding. CONCLUSIONS: The results of this study show that the percentage of patients at high risk for stroke and bleeding is very high. The study revealed that this could be attributed to the high prevalence of modifiable risk factors for stroke and for bleeding in Saudi patients with AF.